The Nigerian civil war of 1967 and the stigmatization of children born of rape victims in Edo State Nigeria (2009)
The history of the Nigerian civil war of 1967-1970, though short, still lingers in the memory of many Nigerians especially communities that were not among the many ethnic groups in the war, hence they were seen as saboteurs. For this many atrocities were netted on them; among which was rape. Up till date, it is still obvious in some of the names given to children now adults born of rape victims by the Biafran and Nigerian army during the two and half years the war lasted. This study therefore seeks to observe the attitude of ‘children’ born this period in question as a result of the stigma attached to their names; it examines community responses to incidence of rape and the level of compensation to mothers (rape victims) and the resultant children born after the war. The study employed principally qualitative methodology: in-depth interview and focus group discussion, among a cross section of 50 households drawn randomly and via a snowballing sampling method in three local government areas of Edo state Nigeria. Major findings from the study showed that 40years after the Civil War, ‘children’ were still seen as ‘bad omen’ mostly affected were the female ‘children’ now married 73% of them. Also observed was that many of the males (67%) have changed their names from war related meanings. The study concludes that rape in war times is evil and should not be encouraged in any form. Finally the study recommends that proper education and enlightenment campaign about the aftermath of rape should be given to soldiers preparing for war.